Challenges and Future Implications for Ophthalmologists in COVID-19 Environment: Doi: 10.36351/pjo.v37i4.1254 - Gull, Ambreen; Noor, Maryam; Khan Niazi, Fuad Ahmad (Pakistan Journal of Ophthalmology, 2021)
In this brief communication, we have highlighted the challenges confronted by Ophthalmologists during COVID-19 pandemic and formulated steps to develop a comprehensive strategy towards minimizing risk of infection transmission between health care workers and patients. To reduce the risk of cross infection, screening and triaging of the patients was done at very initial stage with only high risk patients (red category) were seen directly on slit lamp biomicroscope with PPE. Green and yellow category (low risk) patients were seen via teaching aids or LCDS and telemedicine methods. Elective surgeries were postponed. Less number of attendants were allowed with the patients. Continued teaching services for undergraduate and post graduate students were done by online methods like zoom or Microsoft teams meeting. Departmental meetings were planned via video conferencing (zoom or Microsoft teams). Recommendations are made in this article to ensure safe access to specialized health care in face of COVID-19 pandemic. Key Words: COVID-19, Personal Protective Equipment, Ophthalmologists, Pandemic, Health care workers.